Effect of Dasamuladi Yog and Snigdha Agnikarma in Management of Gridhrasi(Sciatica) - Sarmah, Pratibha; Sarma, Bishnu Prasad; Kalita, Ranjan (International Research Journal of Ayurveda & Yoga, 2022)
Background: Gridhrasi in ayurveda mentioned under vataja nanatmaja vyadhi, with pain, numbness and heaviness being the most common feature along the course of sciatic nerve distribution starting from sphik,kati , prushtha, uru,janu, jangha till pada, Sciatica lately has become a very troublesome disease to a mass people and seemed to be increasing irrespective of gender, due to unhealthy and haphazard lifestyle. Modern medicine and surgical intervention are yet to provide a promising result, while ayurveda has opted different treatment principles for the same. Aims and objectives: Clinical study to rule out the efficacy of dasamuladi yog and snigdha agrikarma in management of gridhrasi(sciatica). Materials and methods: a randomized clinical study was done on a total of 80 number of patients diagnosed with sciatica, attending Kayachiktsa Department, in Govt. Ayurvedic College and Hospital,Guwahati. Oral intervention with Dasamuladi yog and therapeutic intervention of Snigdha agnikarma for a period of 30 days, was provided with follow up of 15 days apart. Result: Significant changes noted in 1st follow up, marked improvement in different symptoms were noted after completion of treatment. Conclusion: the proposed therapy can be effective and adopted as an alternative approach to treat sciatica.